A Correlational Study of the Bahtsul Masail Method, Learning Motivation, and Students’ Understanding of Islamic Law - Husnawadi, Husnawadi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This study addresses the limited empirical investigations into the correlation between traditional Islamic learning models and student academic outcomes in higher education, specifically within the context of Islamic legal education. The purpose of this research was to analyze the relationship between the Bahtsul Masail method, learning motivation, and students’ understanding of Islamic law among fourth-semester students in the Ahwal al-Syakhsiyah program at IAIH NW Lombok Timur. A quantitative correlational approach was employed, involving a purposive sample of 53 students. Data were collected utilizing validated questionnaires and comprehension tests on Islamic law, subsequently analyzed through descriptive statistics and Pearson’s Product-Moment Correlation. The findings indicated that the implementation of the Bahtsul Masail method (M=78.5), students' learning motivation (M=81.2), and their understanding of Islamic law (M=76.4) all fell within the